THE EFFECT OF FUEL OIL PRICES AND MONEY SUPPLY ON INFLATION IN THE SUMATERA REGION - Sella Veronika; Valeriani, Devi; Sumiyati (Riau International Conference on Economics, Business and Accounting, 2024)
The purpose of this study was to analyze and determine the effect of fuel oil price and money supply on inflation in the Sumatera Region. Using a quantiative appoarch with secondary data. The analysis techique used is panel data regression. The result showed that simultaneously the price of fuel oil and money supply had a positive and significant effect on inflation in the Sumatera Region. Partially, the price of fuel oil has a positive and significant effect, while the money supply has a negative and instignificant effect inflation on in the Sumatera Region.